Clinical utility of plasma progesterone and blood and plasma glucose concentrations in predicting parturition in Holstein cows - Hiew, Mark Wen Han; Megahed, Ameer A.; Horstman, L. A.; Constable, Peter D. (Elsevier, 2020)
An accurate, practical, and low-cost method for predicting parturition is urgently needed in the dairy industry. The objective of this study was to evaluate changes in plasma progesterone concentration ([prog]) and glucose concentration in whole blood ([gluc]b) and plasma ([gluc]p) as predictors of parturition within 6, 12, and 24 h in primiparous and multiparous Holstein cows. Blood samples were obtained daily at approximately 0900 h from 34 primiparous and 72 multiparous Holstein cows in late gestation and the time of calving recorded to the nearest hour. Plasma [prog] was measured using an ELISA, and [gluc]b and [gluc]p using a low-cost point-of-care glucose meter. The optimal cut-point for predicting parturition was determined using binomial logistic regression with general estimating equations, because the data set consisted of repeated measures for each cow. Diagnostic test performance was evaluated by comparing the area under the receiver operating characteristic curve (AUC) and calculating the sensitivity, specificity, and κ at the optimal cut-point for predicting parturition. Plasma [prog] was the most accurate predictor of parturition within 24 h (AUC = 0.96) and 12 h (AUC = 0.93), whereas [gluc]b was the most accurate predictor of parturition within 6 h (primiparous, AUC = 0.96; multiparous, AUC = 0.86). We conclude that a decrease in plasma [prog] is currently the most accurate test for predicting calving within 24 h. Measurement of [gluc]b is a promising new test for the cow-side prediction of parturition in dairy cows due to its accuracy, practicality, and low cost.